Early Orchiopexy in Undescended Testis – Outcome of Surgical Management in a Tertiary Care Center - K L Aravind; N Nisha; M Ravishankara (Indian Journal of Child Health, 2021)
Introduction: Undescended testis (UDT) is a common congenital problem encountered in pediatric age group. Boys with UDT may have an increased incidence of testicular hypoplasia, atrophy, infertility, torsion of testis, trauma, and testicular malignancy. Hence, there is a need for locating testis and its placement in the scrotum at an early age. Materials and Methods: This was a retrospective study, conducted in a tertiary care center in South India. Data were collected from the medical records and follow-up details of 46 patients who underwent evaluation and surgical management for cryptorchid testis between December 2018 and May 2020. Details were collected regarding history, investigation results, details of surgery, and any intraoperative or post-operative complications. Results: The most common age group presenting with UDT in the current study was 9–12 years with 34.79% (16 children). The overall procedure-related success rate for orchiopexy was 97.5%. In the younger age group of 9 months–6 years, all the UDT were placed into scrotal position, without any volume loss in the short-term follow-up. All the orchiectomies performed were in children aged beyond 6 years. Conclusions: Orchiopexy needs to be completed by 12 months of age for higher salvageability of testicular units as per the current evidence. However, in view of a significant number of late presenters with a higher rate of testicular loss, there is a need for strengthening of referral system for early referral. Standardized surgical approach, utilization of laparoscopy in managing intra-abdominal testis, and optimal timing of orchiopexy are the key to increase the salvageability of testicular units.